The myth of cobra venom cytotoxin: More than just direct cytolytic actions. (June 2022) - Hiu, Jia Jin; Yap, Michelle Khai Khun
Abstract: Cobra venom cytotoxin (CTX) is a non-enzymatic three-finger toxin that constitutes 40–60% of cobra venom. Thus, it plays an important role in the pathophysiology of cobra envenomation, especially in local dermonecrosis. The three-finger hydrophobic loops of CTX determine the cytotoxicity. Nevertheless, the actual mechanisms of cytotoxicity are not fully elucidated as they involve not only cytolytic actions but also intracellular signalling-mediated cell death pathways. Furthermore, the possible transition cell death pattern remains to be explored. The actual molecular mechanisms require further studies to unveil the relationship between different CTXs from different cobra species and cell types which may result in differential cell death patterns. Here, we discuss the biophysical interaction of CTX with the cell membrane involving four binding modes: electrostatic interaction, hydrophobic partitioning, isotropic phase, and oligomerisation. Oligomerisation of CTX causes pore formation in the membrane lipid bilayer. Additionally, the CTX-induced apoptotic pathway can be executed via death receptor-mediated extrinsic pathways and mitochondrial-mediated intrinsic pathways. We also discuss lysosomal-mediated necrosis and the occurrence of necroptosis following CTX action. Collectively, we provided an insight into concentration-dependent transition of cell death pattern which involves different mechanistic actions. This contributes a new direction for further investigation of cytotoxic pathways activated by the CTXs for future development of biotherapeutics targeting pathological effects caused by CTX. Graphical abstract: Image 1 Highlights: Cytotoxin exhibits biophysical interaction with cell membrane. Cytotoxin induces caspase-dependent extrinsic and intrinsic apoptosis. Cytotoxin triggers lysosomal-mediated necrosis. The occurrence of necroptosis has also been observed in cytotoxin-treated cells. Transition of cell death pattern from apoptosis to necrosis or necroptosis is concentration-dependent.